George Pachymeres’ Walking as a Problem - Evgeny Stelnik (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. In George Pachymeres’ historical work, “walking” turns out to be synonymous with a certain political situation. Certainly, the conflict between Michael VIII and Patriarch Arsenius is a peculiar nerve of the Byzantine historian’s historical narrative, and the Arsenite controversy is a significant problem for the Byzantine state, society, and church. In this sense, the “insignificant” “walk” seems to be a fairly accurate metaphor for the emerging political conflict, expressing certain power relations. Such a walk is nothing less than “the will to power in a discursive state.” In other words, Pachymeres’ walking man resolves issues of power by his very movement. Methods and materials. Walking as an act of everyday life has been scrutinized in contemporary cultural studies literature. From a structuralist perspective, to walk is to “speak.” Walk, in this sense, is a whole implicit sign system, with its own signs, structure, rhythm, and context. Walking turns out to be an important social gesture. In this sense, the tired but still walking patriarch of Nicaea, Arsenius the Autorianus (c. 1200–1273), should be properly understood. Analysis. This “walking” is an exceptionally vivid gesture (especially vivid in that the patriarch, not a young man at all, does not stop in his persistence even at night). Before us is not just a personal offense of Arsenius, a man who was deceived and betrayed. It is worth noting that Arsenius himself was regent under John Lascaris, and his inert patriarchal administration, actively issuing documents confirming the privileges of the monasteries, was the only legitimate authority. Such a movement of Arsenius was not so much a protest against the removal of the minor John Laskaris and usurpation of power by Michael VIII but also a defense of his authority. Results. The walking patriarch in George Pachymeres is certainly a very personal moment in the narrative. In fact, an ancient hero appears before us, challenging Fate (and Michael VIII Palaeologus, according to Pachymeres, is simply the evil Rock of the Empire) without hope of victory, where the very tragedy of the situation only emphasizes its heroism and exclusivity.